Accesslaw annotations on Philippine statutes, v. 2 public law (the laws on the state structure, powers, relations and regulations). - Accesslaw, Inc. (Firm). ([Manila] Accesslaw)
Volume 2 of the Laws Annotated series, this is a full-text database of Philippine laws of permanent and general application, organized by section. Links can be accessed to check on the present status of the law as well as its statutory history.
System requirements: 486 or higher (Pentium-class recommended); 16MB RAM for Win95 (32MB recommended), 32MB for Win98/NT (64MB recommended); Windows 95/98/NT or later; 28MB hard disk space; 4x CD-ROM drive (20x or higher recommended).
Keywords: Public law -- Philippines; Philippines (Republic) -- Laws, statutes, etc; Annotations and citations (Law) -- Philippines